Implementasi Metode Tsukamoto Pada Sistem Inferensi Fuzzy - Bara'langi, Stefany Yunita (TEMATIKA, Journal of Informatics and Information Systems, 2013)
Tsukamoto is a method of fuzzy inference system using a weighted average of the if-then rules. It was can be used to soft skills assessment. It was not carried out strictly like truth value in boolean logic (True or False). Assessment of student’s soft skills by drafting rules based on assessment factors and calculate the value of the predicate of each rule to obtain the value weighted averages. Membership function is described by a linear function of representation